Extracellular vesicles derived from dental follicle stem cells regulate tooth eruption by inhibiting osteoclast differentiation - Meng Sun; Meng Sun; Yiru Yu; Yiru Yu; Weixing Zhang; Yi Ding; Yi Ding; Ang Li; Ang Li; Ye Li (Frontiers in Cell and Developmental Biology)
Tooth eruption as a crucial part in tooth development and regeneration is accompanied by ongoing osteogenesis and osteoclast activity. The dental follicle (DF) surrounding the developing tooth harbors dental follicle stem cells (DFSCs) which play a crucial role in maintaining bone remodeling. However, the mechanisms through which they regulate the balance between osteogenesis and osteoclast activity during tooth eruption remain poorly understood. Notably, extracellular vesicles (EVs) in bone homeostasis are considered essential. Our study revealed that the DFSCs could modulate tooth eruption by inhibiting osteoclast differentiation via EVs. Further investigation showed that EVs from DFSCs could inhibit osteoclast differentiation through the ANXA1-PPARγ-CEBPα pathway. Animal experiments indicated that EVs from DFSCs and the cargo ANXA1 affected tooth eruption. In summary, this study suggests the critical role of the dental follicle in tooth eruption through EVs, which may provide therapeutic targets for abnormal tooth eruption and effective approaches for the eruption of regenerated teeth.